Mathematical mechanics from particle to muscle - Cooper, Ellis D. (Singapore World Scientific, 2011)
This title offers all the details of the mathematical mechanics underlying modern modeling of skeletal muscle contraction. The aim is to provide an integrated vision of mathematics, physics, chemistry and biology for this one understanding.
Ground & Foundation of Mathematics -- Calculus as an Algebra of Infinitesimals -- Algebra of Vectors -- Particle Universe -- Introduction to Timing Machinery -- Stochastic Timing Machinery -- Algebraic Thermodynamics -- Clausius, Gibbs & Duhem -- Experiments & Measurements -- Chemical Reaction -- Muscle Contraction.
Keywords: Mechanics, Analytic; Dynamics of a particle -- Mathematical models; Muscle contraction -- Mathematical models; Mathematical physics